VOLTAMMETRY UNDER HIGH-MASS TRANSPORT CONDITIONS - THE HIGH-SPEED CHANNEL ELECTRODE AND HETEROGENEOUS KINETICS - Rees, N; Alden, J; Dryfe, R; Coles, B; Compton, R (1995)
The application of the high-speed microband channel electrode to the study of fast heterogeneous electron transfer kinetics is described. The necessary theory relating the voltammetric wave shape to the standard electrochemical rate constant, k0, the cell geometry, and the solution flow rate is given. Experiments utilizing the one-electron reduction of benzoquinone in acetonitrile solution, containing 0.1 M tetrabutylammonium perchlorate (TBAP) as supporting electrolyte, at a 5 μm platinum microband electrode gave a value of k0 equal to 0.30 (±0.04) cm s-1, in excellent agreement with independent measurements reported for the same system. The results of further experiments on the previously unstudied electrode kinetics associated with the reduction of 3,3′-dibromobenzophenone in 0.1 M TBAP/dimethylformamide solution are presented. © 1995 American Chemical Society.